Integration of Multicultural Education in the ISMUBA Curriculum and Its Implementation in Learning - Mukarom, Mukarom; Assaraj, Qarashat Mohammed Shakir Ali (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
This study aims to explore the Multicultural education content in the ISMUBA curriculum and its implementation in learning at SMA Muhammadiyah 4 Bandung City. Using a qualitative descriptive method, the research describes conditions in curriculum documents and field observations related to learning. Data were collected through observation, interviews, and documentation, and analyzed using data triangulation by reducing, presenting, and concluding the data. The findings reveal that the ISMUBA curriculum, which is unique to educational institutions under Muhammadiyah, is an integrative-holistic modern Islamic education system developed to meet community needs. Based on decree 98/KEP/I.4/F/2017, the curriculum focuses on instilling faith, piety, and strong Islamic values, rooted in the Qur'an and Hadith. Multicultural education is embedded in the curriculum’s structure, process, teachers, and assessments. Implementation at SMA Muhammadiyah 4 involves face-to-face learning, habituation, structured and unstructured independent activities, fostering Islamic character, honesty, care, politeness, and responsibility. Abstrak: Penelitian ini bertujuan untuk mengkaji pendidikan multikultural dalam kurikulum ISMUBA serta penerapannya dalam pembelajaran di SMA Muhammadiyah 4 Kota Bandung. Penelitian ini Menggunakan metode deskriptif kualitatif, penelitian ini menggambarkan kondisi dalam dokumen kurikulum dan hasil observasi di lapangan terkait pembelajaran. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, serta dianalisis menggunakan triangulasi data dengan mereduksi, menyajikan, dan menarik kesimpulan. Temuan menunjukkan bahwa kurikulum ISMUBA, yang merupakan kekhasan lembaga pendidikan di bawah naungan Muhammadiyah, adalah sistem pendidikan Islam modern yang integratif-holistik yang dikembangkan untuk memenuhi kebutuhan masyarakat. Berdasarkan SK 98/KEP/I.4/F/2017, kurikulum ini berfokus pada penanaman keimanan, ketakwaan, dan nilai-nilai Islam yang kuat, yang berakar pada Al-Qur'an dan Hadits. Pendidikan multikultural tercermin dalam struktur, proses, tenaga pengajar, dan penilaian dalam kurikulum tersebut. Penerapan di SMA Muhammadiyah 4 mencakup pembelajaran tatap muka, pembiasaan, tugas terstruktur, dan aktivitas mandiri yang tidak terstruktur, yang bertujuan membentuk karakter Islam, kejujuran, kepedulian, kesantunan, dan tanggung jawab.